Inclusive Curriculum Management: Integrating Diverse Needs In Learning - Sentryo, Izlan; Kamil Muttaqin, Sopian; Rifaldi, Muhammad (Jurnal Ilmu Pendidikan, 2024)
Inclusive education emphasizes the right of every learner to access quality education regardless of background, ability, or special needs. However, the implementation of inclusive practices in Indonesia remains inconsistent, particularly in the area of curriculum management the central component determining how inclusion is translated into classroom practice. This study examines the role of Inclusive Curriculum Management (ICM) in enhancing student participation and learning outcomes by focusing on the development, implementation, and evaluation of curricula that accommodate learner diversity. Employing a survey method with an experimental approach, the study involved 120 participants (30 teachers and 90 students) from three inclusive elementary schools in Kendari City. Quantitative data were collected through structured questionnaires and analyzed using descriptive statistics, t-tests, ANOVA, and linear regression, while qualitative data from interviews were analyzed thematically and integrated through triangulation. The results reveal a significant improvement of 22% in student participation after implementing inclusive curriculum strategies. Teacher interviews highlight that professional training, collaboration, and administrative support are key enablers of successful inclusion. Conversely, limited resources and uneven teacher readiness remain major barriers. The findings confirm that well-managed inclusive curricula characterized by flexible planning, differentiated instruction, and fair evaluation are crucial for achieving equitable learning outcomes. This research contributes empirically and practically to inclusive education discourse, offering strategic insights for policymakers, educators, and administrators to strengthen inclusive curriculum implementation in Indonesia’s educational system.